Trends in the Utilization of Sodium Hyaluronate Eye Drops, Including Disposable and Multiuse Forms, in South Korea: A 14-Year Longitudinal Retrospective Cohort Study - Son, Kyung-Bok (Frontiers in Pharmacology, 2020)
Introduction: Sodium hyaluronate eye drops are frequently prescribed for dry eye disease in South Korea. Objectives: This study analyzed the trends in the utilization of sodium hyaluronate eye drops and evaluate the impact of the introduction of high priced disposable forms in the South Korean market. Methods: The yearly claims data for sodium hyaluronate eye drops from 2002 to 2015 were retrieved from the National Health Insurance Service-National Sample Cohort. Prescriptions of sodium hyaluronate eye drops were sorted by the characteristics of patients and health care institutions. Results: The number of prescriptions have continuously increased and the share of disposable forms reached 37% in 2015. Particularly, the prevalence of prescriptions (general users) has increased during the study period from 2,562/100,000 persons in 2002 to 14,732/100,000 persons in 2015, while the incidence of prescriptions (new users) has remained steady during the study period, approximately 3,500/100,000 persons. More female patients were noted in terms of general users and new users, and the proportion of male patients was higher in new users than in general users. Furthermore, the average age of general users increased during the study period, while that of new users decreased. Finally, the distribution of prescription category was significantly different between sex and age groups in frequently prescribed users. Conclusions: Eye drops in disposable forms, which are safe more convenient to use and carry, have expanded the market in South Korea and caused a financial burden for the insurer as well as for patients. Thus, the utilization of eye drops should be closely monitored from the perspectives of health-care financing and health equity.